Monitoring and Evaluation of Land in Africa framework - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The MELA framework was successfully piloted in Madagascar, Malawi and Tanzania through 2019. Late 2020, plans were made to apply the framework to Intergovernmental Authority on Development (IGAD) countries in 2021.